Amandemen Konstitusi untuk Mengelola Kebhinnekaan Indonesia - Purwo Santoso (Jurnal Ilmu Sosial dan Ilmu Politik, 2007)
Given the flaw of constitutional mandate in establishing The Nanional Board of Local Representative (Dewan Perwakilan Daerah, konwn as DPD), the demand forn further Amanding the countitution has been mounting. This article is in line which idea, nonetheless instituional capacity building should serve as prerequirement. Unless the institution is institutionally competent granting it with more power is risky.